Mixed Phase Solid‐State Plastic Crystal Electrolytes Based on a Phosphonium Cation for Sodium Devices. Issue 2 (22nd September 2016) - Makhlooghiazad, Faezeh; Gunzelmann, Daniel; Hilder, Matthias; MacFarlane, Douglas R.; Armand, Michel; Howlett, Patrick C.; Forsyth, Maria
Abstract : Na batteries are seen as a feasible alternative technology to lithium ion batteries due to the greater abundance of sodium and potentially similar electrochemical behavior. In this work, mixed phase electrolyte materials based on solid‐state compositions of a tri methylisobutylphosphonium (P111i4 ) bis( tri fluromethanesulphonyl)amide (NTf2 ) organic ionic plastic crystal (OIPC) and high concentration of NaNTf2 that support safe, sodium metal electrochemistry are demonstrated. A Na symmetric cell can be cycled efficiently, even in the solid state (at 50 °C and 60 °C), for a 25 mol% (P111i4 NTf2 )–75 mol% NaNTf2 composition at 0.1 mA cm −2 for 100 cycles. Thus, these mixed phase materials can be potentially used in Na‐based devices under moderate temperature conditions. It is also investigated that the phase behavior, conductivity, and electrochemical properties of mixtures of NaNTf2 with this OIPC. It is observed that these mixtures have complex phase behavior. For high compositions of the Na salt, the materials are solid at room temperature and retain a soft solid consistency even at 50 °C with remarkably high conductivity, approaching that of the pure ionic liquid at 50 °C, i.e., 10 −3 –10 −2 S cm −1 . Abstract : A new class of solid‐state electrolyte with high concentration of Na salt is illustrated. A major breakthrough is achieved in 75 mol% NaNTf2 in P111i4 NTf2 OIPC with high conductivity at moderate temperatures where the material exists in a mixed phase state. The presence of a mobile sodium‐containing phase supports high conductivity and consequently high electrochemical stability.